The Influence of Facilities and Service Quality on The Loyalty of Tourists Staying at Harris Riverview Kuta-Bali Hotel - Hedy Wartana, I Made (Akademi Komunitas MAPINDO, 2024)
In the world of hospitality there are many things that can affect the development of the business. One of them is how and the hotel's efforts can attract the attention of consumers and make consumers feel at home with the hotel's services. There are factors that affect customer satisfaction, namely facilities and service quality. In business competition, service becomes the most important thing for companies to differentiate when companies sell the same products as competitors. In order to obtain superior standards in the existing competition, each company must create satisfaction for its consumers in a way that is relevant to the services offered to consumers. Customer satisfaction can be obtained through the facilities and quality of service provided so that consumers can feel comfortable and can feel the expected utility as well as what is done by the Harris Riverview Kuta Bali Hotel. The formulation of the problem in this study is: 1) Is there an influence between facilities on the loyalty of tourists staying at Harris Riverview Hotel Kuta – Bali. 2). Is there any influence between the quality of service on the loyalty of tourists staying at Harris Riverview Kuta-Bali Hotel? 3). How much influence do facilities and service quality have on tourists staying at Harris Riverview Kuta-Bali Hotel?. Based on the results of the analysis obtained shows that 1). There is a positive and significant influence between facilities on the loyalty of tourists staying at Harris Riverview Kuta Hotel – Bali with a regression coefficient value of 0.421 and t test results with a calculated value of 5.774 greater than the ttable value of 1.666, with a value (sig.) of 0.000 smaller than .2). There is a positive and significant influence between the quality of service on the loyalty of tourists staying at Harris Riverview Kuta Hotel - Bali with a regression coefficient value of 0.231 and the t-test results with a calculated value of 3.203 greater than ttable of 1,666 with a value (sig.) of 0.002 smaller than .3). The contribution of the magnitude of the influence between facilities and service quality on the loyalty of tourists staying at Harris Riverview Kuta Hotel - Bali was 57.8% while the remaining 42.2% was influenced by other variables that were not. Keywords: Facilities, Quality of Service and Tourist Loyalty